THE ECOLOGY OF WAR: MONITORING WILDFIRES AND TOXIC EMISSIONS IN UKRAINE - Mahlovana, Tetiana (Collection of scientific papers «ΛΌГOΣ», 2025)
Ongoing military operations in Ukraine have caused severe damage not only to human livelihoods but also to ecosystems. Hostilities have increased the risk of catastrophic failures at industrial sites and critical infrastructure [1]. Beyond the tragic civilian toll, the conflict has triggered transboundary environmental and biomedical consequences [2]. A major result of the hostilities is widespread chemical contamination of air, soil, and water [3]. About 30% of Ukraine’s territory is now contaminated by landmines and unexploded ordnance